2021
DOI: 10.1186/s12885-021-09009-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypoxia on PD-L1 expression in bladder cancer

Abstract: Introduction Recent data has demonstrated that hypoxia drives an immunosuppressive tumour microenvironment (TME) via various mechanisms including hypoxia inducible factor (HIF)-dependent upregulation of programmed death ligand 1 (PD-L1). Both hypoxia and an immunosuppressive TME are targetable independent negative prognostic factors for bladder cancer. Therefore we sought to investigate whether hypoxia is associated with upregulation of PD-L1 in the disease. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…This is in accordance with a previously reported study by Xu et al [24]. Similar results have been reported in other types of tumors, like bladder cancer and glioblastoma [25,26]. An important finding was also the association of HIF1α with low infiltration of PCs with TILs in accordance with previous studies in breast and head-neck cancer [27,28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with a previously reported study by Xu et al [24]. Similar results have been reported in other types of tumors, like bladder cancer and glioblastoma [25,26]. An important finding was also the association of HIF1α with low infiltration of PCs with TILs in accordance with previous studies in breast and head-neck cancer [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with a previously reported study by Xu et al [ 24 ]. Similar results have been reported in other types of tumors, like bladder cancer and glioblastoma [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found that the expression of PD-L1 on RPMI8226-HA cells was lower than that of RPMI8226-Normo cells (data not shown). Smith et al demonstrated that PD-L1 expression in bladder cancer was decreased under hypoxic conditions (31). These observations are in agreement with our data.…”
Section: Figure 5 Expression Levels Of Mevalonate-pathway-related Pro...supporting
confidence: 94%
“…However, only one (B16-F10 melanoma) of four murine cell lines studied showed an increase in the percentage of PD-L1 positive cells after culture in 0.1% oxygen. A study of the effect of hypoxia on PD-L1 expression in bladder cancer observed that hypoxia reduced PD-L1 expression and PD-L1 expression further decreased with increasing cell seeding density ( 24 ). It seems that the hypoxia-induced regulation of PD-L1 is tissue specific ( 12 , 22 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of the effect of hypoxia on PD-L1 expression in bladder cancer observed that hypoxia reduced PD-L1 expression and PD-L1 expression further decreased with increasing cell seeding density ( 24 ). It seems that the hypoxia-induced regulation of PD-L1 is tissue specific ( 12 , 22 , 24 ). E-cadherin is a tumor suppressor protein involved in cell-to-cell adhesion, and its suppression is a typical characteristic of epithelial-to-mesenchymal transition (EMT) induction ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%